تلقي الأنا الشعرية وتشكلاتها عند المتنبي - طريلي, عفاف; راجح, سامية (جامعة الوادي - university of Eloued, 2021)
يهدف هذا البحث إلى معرفة كيفية تلقي الأنا في شعر المتنبي، وتشكلها، و حضورها في نصه الشعري، كما يرصد تحولات الأنا وتفاعلها مع واقعها، وانعكاس التجربة الشعرية على ذهن المتلقي، لإشراكه في انفعالها الشعوري نحو الآخر، ودلالاتها الأسلوبية والموضوعية، التي تأبى الاحاطة والتأطير رافضة مظاهر الزيف والخداع، بصور فنية مختلفة. This research aims at knowing the reception of poetic ego and its formations in Al-Mutanabi's poetry, and its presence in his poetic texts. It is also designed to figure out ego transformations and its reaction with its fact. Moreover, the research deals with the reflection of the poetic experience on the receiver's mind, as to integrate him in its emotional excitement towards the other and its stylistic and thematic connotations which deny the briefing and framing and negating the appearances of fake and deception by means of different.
مقال
Keywords: التلقي؛ الأنا الشعرية؛ التشكيل الفني؛ الكتابة الإبداعية، القراءة; the reception; poetic ego; artistic formation; creative writing; reading